Azamacrocycles and tertiary amines can be used to form size tuneable hollow structures or monodisperse oxide nanoparticles depending on the 'M' source. Issue 41 (1st July 2019) - Tilburey, Graham E.; Blundell, Toby J.; Argent, Stephen P.; Perry, Carole C.
Abstract : 1, 4, 8, 11-Tetraazacyclodecane plus (a) a silicon catecholate ion generates novel hollow tetragonal crystalline materials, and (b) tetramethoxysilane generates amorphous silica sols. Abstract : We show that the azamacrocycle 'cyclam' (1, 4, 8, 11-tetraazacyclodecane) in conjunction with a silicon catecholate ion generates novel hollow tetragonal tube-like crystalline materials [(C6 H4 O2 )3 Si][C10 H26 N4 ]·H2 O, whose dimensions can be tuned according to the pH of the reaction medium. The synthesis approach was successful for both silicon and germanium and we hypothesise that a range of other catecholate precursors of elements such as iron could be used to generate a large array of inorganic materials with interesting morphologies. The synthesis approach can be extended to tertiary diamines with functional group spacing playing an important role in the efficacy of complexation. Of the molecules explored to date, a C2 spacing ( N, N, N ′, N ′-tetramethylethylenediamine (4MEDAE)), leads to the most efficient structure control with hollow hexagonal tube-like structures being formed. In addition, we show that azamacrocycles, in the presence of unbuffered tetramethoxysilane (TMOS) solutions can be used to manipulate silica formation and provide a fast ( ca. 10 minutes) synthesis route to particles whose diameter can be tuned from ca. 20 nm to several hundreds of nm under reaction conditions (no extremes of pH) that make the sols suitable for direct use in biotechnological applications.